"Invitavo Le Creature Tutte Ad Amare Il Sommo Bene": Il "Cantico di frate Sole" nell'esperienza spirituale di Veronica Giuliani vissuta all'interno dell'orto del onastero - Block, Wiesław ca. 21. Jh. (Miscellanea francescana, 2025)
The article refl cts on a significant theme - the spiritual legacy of Saint Francis of Assisi. In the case of the Saint of Assisi and his followers, such as Saint Veronica Giuliani, their experience off ers a profoundly innovative lens through which to view the relationship between the human being and the cosmos. This is not a pessimistic vision of the material world, but a spiritual perception that recognizes in creation a refl ection of the divine presence. Creation thus becomes a sacred place, where the voice of the Creator can still be heard and welcomed in a dialogue of love and gratitude. The spiritual experience of Saint Veronica Giuliani, who lived in the silent and austere daily life within the monastery walls and the monastic garden, fully embraces this vision. It manifests a deep consonance with Saint Francis of Assisi's the Canticle of the Creatures - not merely a poetic affi nity, but a spiritual and theological continuity. Veronica's invitation to all creatures to love the Supreme Good is nothing less than a mystical extension of the Canticle, a cosmic call in which every being is summoned to enter a living and aff ectionate relationship with the Creator.